Integrating Green Economy and Local Wisdom: A Multidisciplinary Strategy for Achieving Sustainable Development in Indonesia - Malikul Habsi (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
The transformation toward sustainable development in Indonesia requires strategies that not only focus on economic aspects but also encompass social, cultural, and environmental values. The green economy emerges as a global approach emphasizing resource efficiency, renewable energy, and the reduction of environmental impacts. However, its successful implementation necessitates integration with local wisdom, which has long guided communities in maintaining ecological balance and social harmony. This study employs a multidisciplinary approach, combining perspectives from economics, environment, society, and culture to analyze the potential integration of the green economy with local wisdom practices in Indonesia. The findings reveal that local wisdom, such as traditional agricultural systems, community-based conservation practices, and the values of mutual cooperation, can strengthen the sustainability of the green economy at the local level. This integration not only enhances the effectiveness of sustainable development policies but also reinforces cultural identity and social resilience. Therefore, a multidisciplinary strategy that combines the green economy with local wisdom is believed to foster inclusive and context-specific sustainable development in Indonesia.